Preliminary assessment of aflp fingerprinting of rubus glaucus benth. elite genotypes (2011)
The Andean blackberry (Rubus glaucus Benth.) is a promissory fruit crop for Colombia with potential to become an international commodity due to its high nutritional and nutraceutical value. Farmer genotypes from the national R. glaucus collection were selected from eight outstanding accessions according to their nutritional and agronomic value, for distribution among local producers. The goal of this work is to evaluate the genomic fingerprint by AFLP analysis of these elite genotypes using three primer combinations. From 179 total amplified loci produced by the three combinations, 20% resulted polymorphic. The EAGG/MCTT combination was the most informative with a 32% polymorphism and greater discrimination power. The genotypes tested showed a high average similarity (96%) and the accessions San Antonio and ILS-1863 formed independent groups with good statistical support in the clustering analysis. The remaining accessions did not form discrete groups with good support (